Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Cryopreservation reduces the Ability to migrate and the Cytotoxicity of natural Killer Cells in 3D: Possible Effects on cellular Immunotherapy - Mark, Christoph; Czerwinksi, T.; Roessner, S.; Mainka, Astrid; Hoersch, F.; Heublein, L.; Winterl, Alexander; Sanokowski, Sebastian; Richter, S.; Bauer, N.; Angelini, T.; Schuler, Gerold; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11